Efficacy of diabetic ulcer severity score in patients with diabetic foot ulcer in predicting prognosis - George, Robinson; Mathew, Joe; L., Vishnu M.; Thomas, Jacob P. (International Surgery Journal, 2021)
Background: Diabetic foot ulcer (DFU) is a full-thickness wound, skin necrosis or gangrene below the ankle induced by peripheral neuropathy or peripheral arterial disease in patients with diabetes. There are well-accepted classification systems for DFUs, namely Wagner’s scoring system, university of Texas scoring system etc. However, only few are scientifically validated. Diabetic ulcer severity score (DUSS) introduced by Beckert et al consists of easily accessible clinical parameters which categorizes wounds into specific subgroups for comparison of outcomes. Methods: A prospective study was conducted on 250 diabetic ulcer patients, attending the out-patient department (OPD) of surgery, Pushpagiri institute of medical sciences, Tiruvalla. Results: Most common age group affected with diabetic foot was between 51-60 years (mean 58.9±10.2 years). Males accounted for 54% of patients. Most common ulcers were of score of 2 followed by score 3. Overall, 105 (42%) of 250 people had amputations in our study with majority undergoing minor amputation (30%) than the major amputation (12%). None of the patients with scores 0, 1 and 2 had major amputation. Probability of healing among the various scores were-100% for score 0, 97.9% for score 1, 83.4% for score 2, 17.7% for score 3 and 4.8% for score 4. Lower score is strongly associated with primary healing and higher score with amputations. Conclusions: DUSS system is an easy wound based diagnostic tool for anticipating probability of healing or amputation and need for surgery by assessing the four clinical parameters and combining them which is safe and easily reproducible.